2016
DOI: 10.1111/clr.12807
|View full text |Cite
|
Sign up to set email alerts
|

The influence of three different apical implant designs at stability and osseointegration process: experimental study in rabbits

Abstract: With the limitations of this animal study, it can be concluded that the design of the apical area influences the implant stability and the bone-to-implant contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
2
15
0
2
Order By: Relevance
“…Nevertheless, benefit–risk evaluation reveals that patients benefit from employed procedures without undergoing extensive additional vertical augmentations. In the present study, the apical implant design was shown to influence implant stability and bone-to-implant contact, which reinforces the findings of Romanos et al [ 16 ] and Gehrke et al [ 59 ]. The expansion procedure presents an additional bicortical anchorage in the oro-vestibular direction (pyramid shape of the alveolar process), which is understood to optimize load resistance [ 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, benefit–risk evaluation reveals that patients benefit from employed procedures without undergoing extensive additional vertical augmentations. In the present study, the apical implant design was shown to influence implant stability and bone-to-implant contact, which reinforces the findings of Romanos et al [ 16 ] and Gehrke et al [ 59 ]. The expansion procedure presents an additional bicortical anchorage in the oro-vestibular direction (pyramid shape of the alveolar process), which is understood to optimize load resistance [ 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…Resonance frequency analysis (RFA) measurement using Osstell Mentor is frequently used to evaluate the implant stability in preclinical and clinical studies [32][33][34]. This technique has been widely used because it is not invasive and does not require extra procedures to obtain the data.…”
Section: Discussionmentioning
confidence: 99%
“…According to Gehrke and co-authors, and in relation to the present study, the apical implant design influences the implant stability and bone-to-implant contact [ 54 ]. The expansion procedure presents an additional bicortical anchorage [ 17 ] in the oro-vestibular direction.…”
Section: Discussionmentioning
confidence: 82%
“…d Opened short expandable dental implant (4.1 × 7 mm). The expanded implant provides an increased bone-to-implant interface ( pyramid shape ) in the apical portion [ 54 ]. e Cross-section view of the implant apex.…”
Section: Methodsmentioning
confidence: 99%